OIL SPILLAGE AND ENVIRONMENTAL DEGRADATION IN NIGER DELTA: EFFECTS ON LIVELIHOOD OF THE HOST COMMUNITIES (Journal of Global Accounting, 2023)
Despite the benefits of oil exploration, oil pollution caused by spillages from the oil industry located primarily in the Niger Delta region has caused the massive destruction to farmlands, sources of drinking water, mangrove forest, fishing grounds and declination of fish, crabs, mollusks, periwinkles and birds. This study evaluates the effect of oil spillage and environmental degradation in the Niger Delta in Nigeria. The specific objectives are to ascertain the effect of environmental degradation on the livelihood of people of Niger Delta region of Nigeria. And to ascertain the effects of oil spillage on the livelihood of people of Niger Delta region of Nigeria. Ex-post facto research design was adopted for this study. This study relied on secondary data extracts from Nigerian Nationap Petroleum Corporation, World Bank Reports, National Buraeu of Statistics, United Nations Environmental Protection Programme for the years 1978 – 1996 being the period that the incidence of oil spillage in Nigeria was at its peak. The data obtained were analyzed using descriptive statistics and multiple regression analysis was used to test the formulated hypotheses computed with the aid of Stata12 statistical software. The study revealed no significant effect of environmental degradation on the livelihood of people of Niger Delta region of Nigeria. Also, it revealed there is a significant effect of oil spillage on the livelihood of people of Niger Delta region of Nigeria. The study recommended that based on the consequences of oil companies’ activities in the region, an integrated approach which is a combination of several development strategies should be employed. That is the establishment of community based integrated approach that needs joint committed efforts from the government and the multinational companies as well as other stakeholders. Also, updating and revising the legislations, reviewing the license of the oil companies and reviewing the fines will go a long way in ensuring compliance, even though the government cannot systematically or frequently monitor these sites.
Keywords: Environmental Degradation; Oil Exploration; Oil Spillage; Pollution